Between Ḥifẓ al-ʿIrḍ (the Protection of Dignity) and Algorithmic Visibility: A Maqāṣid al-Sharīʿah Approach to Digital Modesty in the Age of Self-Commodification - M. Ilham; Muh. Darwis; Munir, Abdulloh; Sudirman; Muhammad Irfan Hasanuddin (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
This article investigates the ethical challenges posed by algorithmic visibility in contemporary digital platforms through the lens of maqāṣid al-sharīʿah, with particular emphasis on the reconceptualization of ḥifẓ al-ʿirḍ (the protection of dignity). While existing studies on digital ethics predominantly rely on secular frameworks, limited attention has been given to how Islamic legal-ethical principles respond to the commodification of the self in platform-mediated environments. This study aims to address this gap by examining how Qur’anic values of modesty (ḥayāʾ) and concealment (sitr) can be reformulated within algorithmic systems that incentivize exposure and self-disclosure. Employing qualitative library research, this study integrates Qur’anic exegesis, contextualist hermeneutics, and a maqāṣid al-sharīʿah approach to develop a normative framework for digital conduct. The findings demonstrate that ḥifẓ al-ʿirḍ must be expanded beyond its classical focus on physical morality to include the governance of digital visibility and self-representation, while also revealing a structural tension between the ethical imperative of dignity preservation and the economic logic of digital platforms that commodify personal identity. This article proposes the concept of digital modesty as an ethical framework rooted in maqāṣid al-sharīʿah, positioning it as a form of ethical resistance against self-commodification, while reaffirming the continued relevance of Islamic legal principles and offering a contextualized normative guide for navigating privacy, intimacy, and visibility in algorithm-driven environments.